State of the Art Lecture on Universal Healthcare - Nishter, Sania (Annals of King Edward Medical University, 2019)
Ladies and gentleman, Assalam-o-alaikum, good morning and congratulations to the organisers of the King Edward Medical College symposium, both for convening this event and for giving it such a befitting theme. Universal health coverage has become the central pillar in the global health discourse. It is the unifying thread in goal three of the sustainable development agenda. It has become the number one policy choice of governments all around the world and for very good reason, because universal health coverage can create avenues to fix broken health systems, it can help to save lives, it can avert death and disability, it can be a vehicle for achieving programmatic goals and most importantly, if it is delivered effectively, it could become the 21st century welfare contract between the state and the citizens, a state's promise to its people.